A METHOD FOR FACILITIES LOCATION AND WEARHOUSE LAYOUT DESIGN: A METHOD FOR FACILITIES LOCATION AND WEARHOUSE LAYOUT DESIGN - Bogdanov, Andrey (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Organizations and enterprises around the world differ greatly in terms of mission, scale, and scope. Yet all of them aim to deploy the best possible network of facilities worldwide for developing, producing, distributing, selling and servicing their products and offers to their targeted markets and clients. Underlying this continuous quest for optimal network deployment is the facility location and layout design engineering.